“The Seven Wonders of the World” from the Russian Academy of Fine Arts Museum in Saint-Petersburg — the Series of Paintings by K. F. Schinkel and K. W. Gropius (New Attribution) - Skvortcova, Ekaterina A. (Actual Problems of Theory and History of Art, 2018)
There is a series of seven large-format paintings (302x231 cm, paper duplicated on canvas, distemper) depicting the Seven Wonders of the World, kept in the Russian Academy of Fine Arts Museum, Saint Petersburg. They now are in need of careful restoration. Since their entering the museum’s collection they have never been either displayed or reproduced (with the exception of “Statue of Jupiter of Olympia” which was restored and presented at the exhibition “Inspired by Greece” in Russian Academy of Fine Arts Museum, Saint Petersburg, 2016). They are mentioned only in one book — “The Germans and the Russian Academy of Fine Arts Catalogue” (“Nemtsy i Akademiia khudozhestv”. Moscow, 2003. In Russian). On the ground of the identity of subject-matter, L. N. Tselishcheva, the author of the catalogue entry, suggests that these paintings could be copies of K. F. Schinkel’s works. German literature on Schinkel as well as Russian newspapers of the mid-19th century which have not been examined in this context confirmed Tselishcheva’s presupposition and enabled us to trace the history of their demonstration in Saint Petersburg in the mid-19th century. These were the copies of Schinkel’s “perspektivische-optische Bilder” (1814) made for Schinkel’s Fest of 1847 (the original paintings were lost during his life) which were sold to Russia. They were purchased by A. L. Roller who demonstrated them in Manezhnaia Square in Saint Petersburg together with “Panorama of Palermo” painted by K. E. Biermann after Schinkel’s sketch as well. The newspapers “Literaturnaia gazeta” and “Severnaia pchela” enrich our knowledge on exhibiting, perception, and estimation of these works in Russia. The critical analysis of German sources (“Zeitschrift fUr Bauwesen”, 1857, “Deutsches Kunstblatt”, 1857, and K. Gropius’s letter to A. Von Wolzogen, 1862) and Russian sources (Literaturnaia gazeta, 1848, and “The Inventory of Paintings of Costume, Sketch, Mannequin, Scenery and Watercolour Classes”) revealed that German ones are more trustworthy in the question of authorship. “The Seven Wonders of the World” from the Russian Academy of Fine Arts Museum should be attributed rather to K. Gropius than to Biermann, and certainly not to Roller. The series are valuable not only per se, but also as a source shedding light on Schinkel’s “perspektivische-optische Bilder”, in general, which have, so far, been known only from few text sources and graphic sketches from Staatliche Museen zu Berlin (some of these sketches were lost in their turn in the World War II and known only from photographs).
Keywords: Seven wonders of the world; Karl Friedrich Schinkel; Andreas Leonhard Roller; Karl Eduard Biermann; Karl Wilhelm Gropius; Russian-German artistic links; theatre decoration; painting; diorama; Russian Academy of Fine Arts Museum; Saint Petersburg